Pengaruh Pengetahuan Kewirausahaan dan Strategi Pemasaran terhadap Pendapatan Pelaku UMKM Kerajinan di Desa Tampaksiring - Sukmapriyanti, Ni Kadek; Dharmayasa, I Putu Arya (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2024)
In carrying out this research activity, the aim of the researcher is to carry out a testing process: (1) the influence that entrepreneurial knowledge has on the income of craft msmes in Tampaksiring Village, (2) the influence that marketing strategy has on the income of crafts msmes in Tampaksiring Village. , and (3) the influence that marketing and marketing strategies have on the income of craft msmes in Tampaksiring Village. This activity uses a type of causal research. The population used by the researchers is craft msmes located in Tampaksiring Village, so the number of samples that support this research is 104. The sampling technique used is the Non Probility Sampling technique, the sampling used is saturated sampling. The method used in carrying out the data collection process is in the form of a questionnaire using multiple linear regression analysis. The hypothesis testing process uses t and F tests using SPSS 25 for Windows. The results obtained from this activity show (1) Entrepreneurial Knowledge shows a positive and significant direction towards Income in craft msmes in Tampaksiring Village (sig. Value 0.000 <0.05), (2) Marketing Strategy shows a positive and significant direction towards Income in msmes actors. Crafts in Tampaksiring Village (sig. Value 0.000<0.05), and (3) The Entrepreneurial Knowledge and Marketing Strategies shows positive and significant results on the income of Craft msmes in Tampaksiring Village (sig. Value 0.000<0.05).